2010
DOI: 10.1007/s10683-010-9255-3
|View full text |Cite
|
Sign up to set email alerts
|

Does trust extend beyond the village? Experimental trust and social distance in Cameroon

Abstract: Experiment, Trust game, Dictator game, Risk game, Social distance, Cameroon, C93, O12, Z13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 24 publications
5
45
0
1
Order By: Relevance
“…Trust can be identified in a between-subjects design with OT using the investment and triple dictator games (Cox 2004). Within-subjects designs with PAI for multiple tasks, such as a risk game and investment game and triple dictator game (Etang et al 2011), cannot identify trust because responses are confounded by portfolio incentives. Use of PAI in such experiments should be avoided in favor of between-subjects designs and OT.…”
Section: Examples Of Experiments On Social Preferencesmentioning
confidence: 99%
“…Trust can be identified in a between-subjects design with OT using the investment and triple dictator games (Cox 2004). Within-subjects designs with PAI for multiple tasks, such as a risk game and investment game and triple dictator game (Etang et al 2011), cannot identify trust because responses are confounded by portfolio incentives. Use of PAI in such experiments should be avoided in favor of between-subjects designs and OT.…”
Section: Examples Of Experiments On Social Preferencesmentioning
confidence: 99%
“…If the sum of an entrepreneur's capital and private wealth is higher than his saving target he exits the angel market segment and is replaced by a random new entrepreneur. 7 11. If investors have no capital left they exit the market and are replaced by a random new investor.…”
Section: Modelmentioning
confidence: 99%
“…6 Moreover, studies using either artificial (e.g., Buchan et al, 2006) or natural identities (e.g., Etang et al, 2011) have shown that in-group favoritism affects both trust and trustworthiness.…”
Section: Conceptual Framework and Conjecturesmentioning
confidence: 99%